Does Infertility Stress Impair Sexual Function in Infertile Women and Men? A Cross-Sectional Study in Iran - Amraei, Samira; Abedi, Parvin; Nikbakht, Roshan; Tadayon, Mitra; Maraghi, Elham (Frontiers in Medicine, 2022)
Background The issue of infertility is a worldwide challenge, estimated to affect around 50 million couples. This study aimed to evaluate the relationship between infertility stress and sexual function in men and women with infertility. Methods In this cross-sectional study, 300 men and women with infertility were recruited. A demographic questionnaire, the Fertility Problem Inventory, the Female Sexual Function Scale (FSFI), and the International Index of Erectile Function (IIEF) were used to collect data. Independent t-test, Chi-square, and linear and logistic regressions were used to assess the data. Results The total score of sexual function in women and men was 22.18 ± 7.86 and 57.7 ± 17.8, respectively. Infertility duration and the ability to pay for the costs of infertility treatment had a significant relationship with sexual function in women. A significant association was found between communication concerns and sexual function scores in men with infertility. Infertile women had more sexual concerns, while infertile men had more communication concerns. Conclusion This study showed that women with infertility had more infertility stress than men with infertility. Women with higher infertility duration and the inability to pay for the infertility treatment costs impaired sexual function. Women with infertility had more sexual concerns, while Men with infertility had more communication concerns. Policymakers need to consider strategies such as counseling for men and women with infertility to help them cope with their problems, especially their psychological problems. The lack of random enrollment of participants and lack of control group were the limitations of this study.